Involvement of community pharmacists in continuing professional development (CPD): a baseline survey in Gondar, Northwest Ethiopia - Dessalegn Asmelashe Gelayee; Gashaw Binega Mekonnen; Mequanent Kassa Birarra (BMC, 2018)
Abstract Background Health care professionals have been striving to maintain their competence to deliver the best quality of service. This study intended to determine involvement in continuing professional development of community pharmacists in Gondar, Northwest Ethiopia. Methods About 46 community pharmacists, each from a different setting, were interviewed using structured questionnaire. Data were analyzed using Pearson's Chi-square test of independence and Mann-Whitney U test with p < 0.05 taken as statistically significant. Results The majority (n = 26, 56.5%) reported of being unaware of the CPD concept. The mean hour spent per week on CPD is 4.1 ± 4.0. Most (n = 34, 73.9%) were engaged in self directed learning and expressed an interest to be more involved in CPD activities (N = 39, 84.8%). Interactive workshops were the most preferred modality. However they seek further support in the process of identifying learning needs (N = 34, 73.9%). The main barriers for CPD engagement include lack of (N = 36, 78.3%) and inaccessibility (N = 34, 73.9%) of CPD opportunities as well as time shortage (N = 33, 71.7%). Conclusions The community pharmacists in Gondar, Northwest Ethiopia lack awareness of CPD concept but engaged in various types of CPD activities. They demonstrated good attitude and seek more support. The main barrier was lack of opportunities related to CPD.